Implementation of Balance Exercise to Improve Physical Mobility and Prevent the Risk of Falls in Elderly Residents in Nursing Homes - Widyawati Dian Lestari; Vivi Sovianti; Maya Cobalt Angio Septianingtyas (Fakultas Keperawatan Universitas Andalas, 2026)
Aging is commonly associated with progressive decline in musculoskeletal function, which leads to reduced physical mobility and significantly increases the risk of falls among the elderly. Therefore, effective interventions are needed to improve balance and mobility to prevent falls and maintain functional independence in this population. The aim of this study was to determine the effect of balance training on increasing physical mobility and reducing the risk of falls. This type of research is a pre-experimental study without a control group. The population in this study was 78 people, the sample in this study was 30 respondents who were selected using purposive sampling techniques based on inclusion and exclusion characteristics. The instruments used were the Elderly Mobility Scale and the Timed Up and Go Test which had been tested for validity and reliability. Data analysis used descriptive statistical tests and the Wilcoxon test. The intervention in this study was balance training, which was performed three times a week. The study found that 66.7% of respondents in the pre-test needed assistance, and 60% of respondents were in the moderate risk of falling. The post-test results showed that all respondents were in the moderate risk of falling (63.3%). The Wilcoxon test showed a significant difference before and after the intervention with a p-value of 0.02 (p < 0.05). Balance exercise effectively improves physical mobility and reduces fall risk among elderly nursing home residents. Future studies should apply longer and more intensive interventions with larger samples and control groups to strengthen effectiveness comparisons.